An in vitro Thyroid Function Test by Res-O-Mat T4 Kit - YONAHARA, Yoshio; KURAMITSU, Ichiro; TAKAHARA, Yoshiko; KIRIMURA, Hiroshi (RADIOISOTOPES, 1971)
Res-O-Mat T4 is an in vitro 124I-T4 diagnostic test used for determining the T4 level of serum by competitive protein binding analysis.“Res-O-Mat T4 Kit”was used 177 cases. The test procedure was examined and the following results were obtained. 1) T4 levels (μg%) : 5.0-12.5 (average 9.10) for 8 normal males, 4.6-12.5 (average 8.1) for 26 normal females, 10.6-20↑ (average 16.3) for 15 cases male with hyperthyroidism, 13.2-20↑ (average 17.7) for 39 cases females with hyperthyroidism, 1.7-5.0 (average 3.5) for 7 cases with hypothyroidism, 4.5-16 (average 8.5) for 49 cases with non toxic goiter, 5.8 and 9.8 for 2 cases of subacute thyroiditis, 4.8-7.8 (average 6.0) for 3 cases of chronic thyroiditis, 9.0 and 10.8 for 2 cases of malignant goiter. The test demonstrated that the levels obtained with hyperthyroid, euthyroid and hypothyroid persons very slightly overlapped. T4 levels in normal subjects were differentiated from those with hyperthyroidism and hypothyroidism. 2) Extraction ratio of T4 from sera were 82.5% in 10°C and 79.5% in 26°C. 3) T4 levels increased as the duration of incubation prolonged and it was considered that the incubation at room temperature for 60 min was the most stable and practical. 4) T4 levels was influenced by high and low temperature. Res-O-Mat T4 Kit doesn't need rinsing of resin and evaporation of alcohol by N2 gas and requires extremely simple procedure.